Zastosowanie analizy korespondencji do klasyfikacji materiałów z późnej epoki brązu na przykładzie obiektów funeralnych z Polski południowo-wschodniej - Rajpold, Wojciech (Folia Praehistorica Posnaniensia, 2020)
It is truism to say that for an archaeologist the question of chronology is particularly important. In relation to Tarnobrzeg Lusatian Culture, this topic was frequently raised, which in the case of its early and late stages gave satisfactory results. There are numerous determinants of these phases, and they can also be divided into smaller periodical stages. The dynamics of change is well understood. However,p hase II is far more problematic. Basically, it is represented by one type of vessel. In addition, the 150–200 year phase is very compact in terms of inventory and it is almost impossible to identify older or younger materials. The problem of its decline also needs to be emphasized, where when treated through the prism of the San River style as it usually is, it should be prolonged to HaD. The author, using the correspondence board, tries to indicate materials which can be related to the older and younger episode of the second phase of Tarnobrzeg Lusatian Culture.